2012
DOI: 10.1209/0295-5075/99/33001
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-number–dependent energy level shifts of ions in dense plasmas: A generalized analytical approach

Abstract: -Dense plasma effects on bound energy levels have been studied with relativistic atomic structure simulations that include intermediate coupling and configuration interaction. A general analytical formula is proposed that predicts the energy of LSJ-split levels for wide conditions of density and finite temperature and any atomic element. The achieved precision of the analytical approach allowed even to describe energy level crossings and the breakdown of level degeneration induced by dense plasma effects. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 22 publications
4
20
1
Order By: Relevance
“…Our measured values at the highest density disagrees with the analytical line shift model developed by Li and Rosmej [28] by a factor of two. Even though the measured shifts between 4 and 6 eV are lower than predicted by this model, they are at least four times larger than the lower limits placed early on on the shift by pioneering work [5], which estimated that the shifts are at least as large as 5% of the line width (> 1 eV in our case).…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…Our measured values at the highest density disagrees with the analytical line shift model developed by Li and Rosmej [28] by a factor of two. Even though the measured shifts between 4 and 6 eV are lower than predicted by this model, they are at least four times larger than the lower limits placed early on on the shift by pioneering work [5], which estimated that the shifts are at least as large as 5% of the line width (> 1 eV in our case).…”
contrasting
confidence: 68%
“…show the predictions from the ion-sphere model proposed by Li and Rosmej (green traces) [28]. This model predicts a linear dependence on the electron density.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The analytical expressions obtained agree with results from direct numerical integration of energies and wavefunctions. Moreover, beyond the hydrogen-like case, the current formalism may be generalized to more complex ions, in the spirit of other works such the work by Li and Rosmej [29]. Finally, to deal with more complex ions, the analytical potential proposed here may be included in parametric potential codes such as FAC [30], as mentioned in our previous work.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a recent measurement of both shift and width of the K β transition of He-like Cl from the ORION laser facility indicated significant disagreement with existing theoretical models [12]. Specifically, it was shown that the recent theoretical line shift model of Li and Rosmej [13] overestimated the energy shift by about a factor of two at electron densities that are inferred from the line widths according to the standard theory of Stark broadening. Clearly, additional theoretical developments are needed to put a potential density diagnostic based on line shifts on a solid footing, and, of course, to provide reliable atomic data for the modeling of the radiative properties of astrophysical and laboratory plasmas.…”
Section: Introductionmentioning
confidence: 99%